A 2200-year-old document of planning history: the border city planning system in Chao Cuo's memorials to the throne. (4th March 2023) - Guo, Lu; Wu, Tinghai
ABSTRACT: A series of memorials to the throne written by Chao Cuo (200–154 B.C.), a high-ranking official of the Western Han Dynasty (206 B.C.–A.D. 24), contained systematic thoughts and methods of border city planning, and could be regarded as a valuable 2200-year-old document of planning history. Based on the textual interpretation of the classical texts, a historical analysis method that mixes theoretical construction and empirical evidence is applied to analyse the planning thoughts and methods proposed in Chao Cuo's works, including the strategic layout of human and land resources at the territorial scale, city site selection based on natural geographical conditions, multi-scale constructions of physical space from region to residence and social governance balancing people's livelihood and military affairs. The purpose of the planning system proposed by Chao Cuo was to build cites that were suitable for both military defence and people's daily lives, so that people would settle in the frontier and form a stable military force to resist enemies. Chao's works explain a typical feature of ancient Chinese city planning as an instrument of political governance, and demonstrated the interaction between urban form and way of life.